2016
DOI: 10.1002/mbo3.338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norspermidine on Pseudomonas aeruginosa biofilm formation and eradication

Abstract: Biofilms are defined as aggregation of single cell microorganisms and associated with over 80% of all the microbial infections. Pseudomonas aeruginosa is a Gram‐negative opportunistic pathogen capable of leading to various infections in immunocompromised people. Recent studies showed that norspermidine, a kind of polyamine, prevented and disrupted biofilm formation by some Gram‐negative bacterium. In this study, the effects of norspermidine on P. aeruginosa biofilm formation and eradication were tested. Microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 53 publications
0
48
0
Order By: Relevance
“…The oligonucleotide primers used to amplify the QS‐related genes ( lasR , rhlR , mvfR , and pqsC/D ) and EPS‐related genes ( pslA , pelA , and alg44 ) were referred to Qu et al. () and Kim, Park, and Lee (), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The oligonucleotide primers used to amplify the QS‐related genes ( lasR , rhlR , mvfR , and pqsC/D ) and EPS‐related genes ( pslA , pelA , and alg44 ) were referred to Qu et al. () and Kim, Park, and Lee (), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This led to reduced attachment to the surface. A smaller number of cells attached to the surface resulted in limited biofilm production and easier eradication (Qu et al 2016). Biofilm formation can be also prevented by applying the analogues of AHL molecules that inhibit QS communication.…”
Section: Mechanisms Of Qs Inhibition-qqmentioning
confidence: 99%
“…Since the field first picked up in 1994, there has been an exponential increase in publication output in the field leading up to 2018, with particularly dramatic increases seen over the past 3–4 years. This is due to the pronounced ability of P. aeruginosa to induce biofilm‐related disease that is causing significant and ongoing concern in the clinical setting, which has spurred increasing research effort in developing strategies that target their control and eradication (Qu et al, 2016). In our study, significant bibliographic coupling was found for publications arising from 820 institutions over 57 countries worldwide, among the almost ten thousand publications in the field that have appeared since 1994.…”
Section: Discussionmentioning
confidence: 99%